Pengaruh Kedisiplinan dan Etos Kerja terhadap Efektivitas Kerja Karyawan pada CV. Pramita Kediri - Witdodari Sulistyo M, Aminah; Suwarsono, Edy; Dian Evasari, Aprilia (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2024)
This research aims to determine the influence of the variables discipline (X1) and work ethic (X2) on work effectiveness (Y) at CV. Pramita Kediri. This type of research is quantitative research which is used to test the relationship of a variable to other variables which emphasizes the analysis on numbers processed using statistical methods. The data collection techniques used are primary data and secondary data. Sample selection used the saturated sampling method, the number of samples in the study was 35 respondents from CV. Pramita Kediri. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. From the results of the research, it shows that the Discipline and Work Ethic variables have an influence on Work Effectiveness at CV. Pramita Kediri. The research results showed that the multiple linear regression equation Y = - 8.752 + 0.834 Work Ethic has a partially significant effect on work effectiveness with a sig result of 0.003 < 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that Discipline and Work Ethic have a simultaneous and significant effect on Work Effectiveness at CV. Pramita Kediri